Dual-Thresholding Based Sinogram Interpolation To Reduce Metal Artefact In Computed Tomography Imaging - Mohamad Sobri, Nurul Fathin (2021)
Metal artefacts can degrade the image quality of computed tomography (CT) images which lead to difficulties and errors in diagnostic analysis. Metal artefacts appear as bright and dark streaks around the metal object. It is caused by beam hardening effects, photons starvation, non-linear partial volume, photon scatter,undersampling and inappropriate correction algorithm during reconstruction of image. The aim of this study is to improve the sinogram interpolation technique for metal artefacts reduction (MAR) in CT images.